2020
DOI: 10.1038/s41419-020-02786-2
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of ADAM9 by N-α-acetyltransferase 10 protein contributes to promoting progression of androgen-independent prostate cancer

Abstract: N-α-Acetyltransferase 10 protein (Naa10p) was reported to be an oncoprotein in androgen-dependent prostate cancer (PCa; ADPC) through binding and increasing transcriptional activity of the androgen receptor (AR). PCa usually progresses from an androgen-dependent to an androgen-independent stage, leading to an increase in the metastatic potential and an incurable malignancy. At present, the role of Naa10p in androgen-independent prostate cancer (AIPC) remains unclear. In this study, in silico and immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…ADAM9 owns shedding and adhesive properties depending on its metalloproteinase and disintegrin domains, respectively [20]. Increased ADAM9 expression has been reported in various cancers, such as hepatocellular carcinoma [21], prostate cancer [22], breast cancer [23,24], non‐small cell lung cancer [25], skin melanoma [26] and glioma [27]. It was reported that the mRNA levels of ADAM9 were positively associated with histological type and tumor grade in human glioma and could act as a prognostic factor in patients with lower‐grade glioma [27].…”
Section: Introductionmentioning
confidence: 99%
“…ADAM9 owns shedding and adhesive properties depending on its metalloproteinase and disintegrin domains, respectively [20]. Increased ADAM9 expression has been reported in various cancers, such as hepatocellular carcinoma [21], prostate cancer [22], breast cancer [23,24], non‐small cell lung cancer [25], skin melanoma [26] and glioma [27]. It was reported that the mRNA levels of ADAM9 were positively associated with histological type and tumor grade in human glioma and could act as a prognostic factor in patients with lower‐grade glioma [27].…”
Section: Introductionmentioning
confidence: 99%
“…In triple-negative breast cancer (TNBC), higher ADAM9 expression correlates significantly with poorer outcomes, while inhibition of ADAM9 expression lowers TNBC cell aggressiveness by suppressing AKT/NF-κB signaling 38 . In androgen-independent PCa, ADAM9 can form a complex with N -α-acetyltransferase 10 protein to maintain ADAM9 protein stability and thus promote tumor cell invasiveness and in vivo tumor progression 39 . ADAM9 also serves as a significant and independent prognostic marker associated with prostate-specific antigen relapse-free survival in PCa patients treated with ADT 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Myosin light chain kinase (MLCK), which plays a central role in controlling actin-myosin interaction, was found to be acetylated and suppressed by Naa10p and thus resulted in decreased cell migration [ 42 ]. In contrast, Naa10p can form a complex with ADAM9 to promote cell invasiveness of androgen-independent prostate cancer [ 43 ]. We have recently identified MMP-2 as an N-terminal acetyltransferase substrate of Naa10p in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%